The Andean bear in Ollachea (Puno, Peru) and the anthropogenic activities threatening its presence - Figueroa Pizarro, Judith (2023)
In the department of Puno, deforestation in the provinces of Sandia, Carabaya, and San Antonio de Putina is increasing, affecting vulnerable species like the Andean bear (Tremarctos ornatus). To determine the areas and habitats used by this bear in Ollachea (Carabaya) and identify the human activities influencing its presence, an assessment was conducted in October 2014, involving a survey of 17.80 km of trails and interviews. Thirty-eight GPS points with species records were identified, ranging from 2009 to 4086 masl, in transitional zones of montane forest-puna (50.00%), montane forest (21.00%), puna (15.80%), and intervened areas (13.20%). These points were located up to 0.72 km from water sources and 1.87 km from the forest. A preference for Eryngium weberbaueri as food was observed. In Ollachea, the Andean bear faces significant pressures due to various human activities. The Interoceanic Highway has made bears more vulnerable to hunting as it has facilitated their visibility when crossing it. Mining has contaminated rivers and streams used by bears as travel routes. Agriculture has generated conflicts as bears sometimes enter cornfields, causing losses. Bear hunting, for the purpose of obtaining pets or meat, also poses a threat. The information obtained in this research will be used to create spatial distribution models in Ollachea to identify critical areas for bear survival and plan conservation and management measures, such as connectivity corridors and priority protection areas.